2015
DOI: 10.1158/1055-9965.epi-15-0068-t
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Meat Mutagens and Risk of Prostate Cancer in a Cohort of U.S. Health Professionals

Abstract: Background Evidence relating heterocyclic aromatic amines (HCA), associated with high-temperature cooking methods, to prostate cancer risk is inconsistent Methods In a large US cohort study, intakes of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) and 2-amino-3,4,8-trimethylimidazo[4,5-f]quinoxaline (DiMeIQx) and a meat-derived mutagenicity index (MDM) were assessed using a cooking method questionnaire administered in 1996. Until 2010, 2,770 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Characteristics of prospective cohort studies of various meat cooking methods, heterocyclic amines, heme iron intake and prostate cancer are shown in Table 3 [ 16 , 18 , 34 , 44 , 47 , 49 , 50 ]. The results for these meta-analyses are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of prospective cohort studies of various meat cooking methods, heterocyclic amines, heme iron intake and prostate cancer are shown in Table 3 [ 16 , 18 , 34 , 44 , 47 , 49 , 50 ]. The results for these meta-analyses are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…of subjects (No. of cases) Age range (mean) Year baseline diet assessed Follow-up, years Meat cooking methods exposures analyzed Heterocyclic amine or heme iron exposures analyzed Prostate cancer outcome Cross et al, 2005 [ 47 ] PLCO (US) 29,361 (1338) 55–74 1993–2001 11 Barbequed meat; panfried meat; very well-done meat DiMeIQx; MeIQx; PhIP; B(a)P; Mutagenic activity Total PCa; incident PCa; advanced PCa Jackszyn 2012 [ 50 ] EPIC (Europe) 139,005 (4606) >30 1989–2004 11 None Heme iron Total PCa, advanced PCa, localized PCa Koutros et al, 2008 [ 34 ] AHS (US) 23,080 (668) 48.3 [mean] 1993–1997 10 Grilled meat; pan-fried meat; broiled meat; rare or medium cooked meat; well and very well done cooked meat DiMeIQx; MeIQx; PhIP; B(a)P; Mutagenic activity Total PCa; incident PCa; advanced PCa Rohrmann et al, 2015 [ 49 ] HPFS (US) 26,030 (2770) 40–75 1996 14 None MeIQx; DiMeIQx; PhIP; Meat-Derived Mutagenicity Index Total PCa, advanced or lethal PCa Sander et al, 2011 [ 16 ] EPIC-Heidelberg (Germany) 9578 (337) 40–65 2002–2004 7 Degree of browning: strong/extreme; light/moderate DiMeIQx; MeIQx; PhIP Total PCa; advanced PCa Sharma et al, 2010 [ 18 ] Multiethnic Cohort (US) 4169 (2106) 45–75 1993–1996 8 Meat preference: medium; well done None Total PCa Sinha et al, 2009 [ 44 ] NIH-AARP (US) 175,343 (10,313) 50–71 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the purple rice extracts not only showed a strongly anti‐mutagenic effect against mutagenesis of selected carcinogens, including PhIp, Glu‐P‐1, and IQ in a dose‐dependent manner, but the purple rice extracts up to 500 µg/plate also did not cause mutagenicity in S. typhimurium strains TA98 and TA100, either with or without the S9 mixture, when compared with the standard mutagens. Although little is known about the relationship between these mutagens and prostate cancer, it has recently been reported that the consumption of PhIP from processed red meat is associated with a higher prostate cancer risk (Rohrmann et al, ). PhIP is a major carcinogen that is generated from cooking meats at high temperatures (Felton et al, ), which causes the formation of DNA adducts that lead to carcinogenesis (Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%